The Effect of Intrinsic Motivation and Job Satisfaction on PT X Employee Performance - Mala Nasikhatun Ni'ma; Lisa Harry Sulistiyowati (Interdisciplinary Social Studies, 2026)
Employee performance is a key factor in determining organizational success, particularly in the era of globalization and increasing business competition. Intrinsic motivation and job satisfaction are considered important internal factors that can influence employee performance. The purpose of this study is to examine how intrinsic motivation and job satisfaction partially (t-test) or simultaneously (F-test) affect the performance of PT X employees as the subjects and population of this study. In this study, the sampling technique used is saturated sampling, which includes 100 employees. The method of data collection is a questionnaire, while the analysis technique employed is multiple linear regression analysis. The results of this study show that intrinsic motivation has a significant positive influence on employee performance, as indicated by the t-value being greater than the t-table value (11.035 > 1.804), while job satisfaction also has a positive and significant influence, as indicated by the t-value being greater than the t-table value (10.042 > 1.804). Simultaneously, the influence of intrinsic motivation and job satisfaction on employee performance is demonstrated by the F-value being greater than the F-table value (138.459 > 3.09). All results, both partial and simultaneous, have significance values of less than 0.05. In conclusion, intrinsic motivation and job satisfaction are important determinants of employee performance at PT X, both individually and collectively. Improving these factors can enhance employee productivity and organizational effectiveness.